Acervos documentais de movimentos sociais: aspectos de memória e identidade cultural no Arquivo da Comissão Pastoral da Terra - Belém - SANTOS, Geovanna Figueiredo dos (2022)
Considering the little visibility of social movements' archives, the focus of this research was the dimension of information present in the archive of the Pastoral Land Commission (CPT) - Belém. The objective of the work was to survey theoretical studies on social movement archives; dimensions of memory and concepts of identity; to present and understand the aspects of the archive of the Pastoral Land Commission and, based on document analysis, to identify the aspects of cultural identity related to the peasant movement in the Paraense Amazon, evidenced by means of this archive. The methodology consisted of bibliographic research in databases and documentary research in the CPT archive. As results, we present the relations between memory, identity, archives and representation, highlight some difficulties faced by the social movements in the countryside, their representation through documentation, the importance of perpetuating the memories of their struggles as a means of achieving their rights, as well as the importance of the identity aspects in the recognition and diffusion of these collections. It was concluded, regarding the context of the documents produced by the CPT, that identity is related to the attribution of meaning, sense and re-signification of human actions registered in the documents.